Analisis Efektivitas dan Implikasi Penerapan Metode Pembelajaran Project Based Learning dalam Konteks Pendidikan Vokasional di Sekolah Menengah Kejuruan: Sebuah Meta-Analisis yang Komprehensif - Ambiyar; Marta, Rizkayeni (The Indonesian Journal of Computer Science, 2024)
This research aims to thoroughly analyze the influence and implications of Project-Based Learning (PBL) on students' critical thinking abilities in the context of vocational education in vocational high schools (SMK). The research method employed is meta-analysis, utilizing a sample of 20 articles from national journals. The instrument used consists of systematically arranged coding categories. The results of the meta-analysis indicate that the impact of Project-Based Learning on students' critical thinking abilities in both vocational high schools (SMK) and general high schools (SMA) is generally positive, but more effective when implemented by students at the SMA level. Additionally, the analysis demonstrates that the use of both real and virtual media in the context of project-based learning has a positive impact on the development of students' critical thinking skills. The implications of these findings are highly relevant for the development of curricula and more effective learning strategies in preparing students to meet the increasingly complex and dynamic demands of the workforce